From the hills to the sea: Mineralogical and chemical characterization of a roof tile assemblage from the Byzantine church at Ashdod-Yam (Israel) - Philip Ebeling; Liora Bouzaglou; Dana Ashkenazi; Johannes H. Sterba; Alexander Fantalkin (Advances in Archaeomaterials)
This paper presents the results of a multidisciplinary approach characterizing roof tiles excavated at the Ashdod-Yam Byzantine church (Israel). Occupied from the late fourth/early fifth century CE, the building was destroyed by fire toward the end of the sixth century CE, sealed by tiles from the roof's collapse. The assemblage of 3846 roof tiles was initially classified through macroscopic and typological analysis. Selected samples were further subjected to optical microscopy of petrographic samples for provenance studies and ceramic technological insights, along with instrumental neutron activation analysis (INAA). The findings reveal the artifacts to be imported from the eastern Mediterranean ophiolitic complexes and from the Judean Hills. Additionally, fragments of painted ceramic roof tiles were tested using scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) to assess the composition of the pigments, examine their microstructures, and understand the manufacturing technologies used. Despite the presence of different types of roof tiles, the paint applied to some of them was found to be uniform, consisting of red, ocher-based pigment, likely sourced locally and applied during the roof's construction. This comprehensive examination on a relatively unexplored type of material sheds new light on specific construction choices during the Byzantine period in the southern Levant.